Impact of Hypertensive Disorders of Pregnancy on the Risk of Stroke Stratified by Subtypes and Follow-Up Time. Issue 2 (February 2022) - Hung, Shih-Kai; Lee, Moon-Sing; Lin, Hon-Yi; Chen, Liang-Cheng; Chuang, Chi-Jou; Chew, Chia-Hui; Yu, Ben-Hui; Yang, Hsuan-Ju; Hsu, Feng-Chun; Chiou, Wen-Yen
Abstract : Background and Purpose: Hypertensive disorders of pregnancy (HDP) comprise 4 subtypes. Previous studies have not investigated the relationship between stroke risk, different HDP subtypes, and follow-up time, which was the purpose of this study. Methods: Data of 17 588 women aged 18 to 45 years who had a history of HDP in Taiwan from 2000 to 2017 was retrospectively reviewed. After matching with confounders, 13 617 HDP women and 54 468 non-HDP women were recruited. Results: HDP women had an adjusted hazard ratio (aHR) of 1.71 (95% CI, 1.46−2.00) for stroke, and 1.60 (1.35−1.89) and 2.98 (2.13−4.18) for ischemic and hemorrhagic stroke, respectively ( P <0.001 for all). The overall stroke risk in the HDP group was still 2.04 times 10 to 15 years after childbirth (1.47−2.83, P <0.001). Although the risks of both ischemic and hemorrhagic stroke persisted, their risk time trends were different. The risk of ischemic stroke reached peak during 1 to 3 years after childbirth with an aHR of 2.14 (1.36–3.38), while hemorrhagic stroke risk gradually increased and had an aHR of 4.64 (2.47−8.73) after 10 to 15 years of childbirth (both P <0.001). Among the 4 HDP subtypes, chronic hypertension with superimposed preeclampsia had the highest stroke risk (aHR=3.86, 1.91−7.82, P <0.001), followed by preeclampsia–eclampsia (aHR=2.00, 1.63−2.45, P <0.001), and gestational hypertension (aHR=1.68, 1.13−2.52, P <0.05); chronic preexisting hypertension had the lowest stroke risk (aHR=1.27, 0.97−1.68, P >0.05). Furthermore, multiple HDP combined with preeclampsia had aHR of 5.48 (1.14−26.42, P <0.05). Conclusions: The effect of HDP on the risk of future stroke persisted for up to 17 years, both for ischemic and hemorrhagic strokes. The presence of multiple HDP and preeclampsia further increase the stroke risk. Abstract : Supplemental Digital Content is available in the text.